Aprendizagem, inovação e comunicação: a dinâmica evolutiva de um plano de emergência nuclear - Quadro, André Luiz Lopes (2014)
The technological development inherent to modern societies has placed human beings in situations of choice from a wide variety of possible risks. As a way to protect people and the environment, actions need to be developed in order to reduce possible consequences of the materialisation of these risks. The thermonuclear power generation demand planning in order to prepare answers to possible emergency situations, as even being considered of low probability of occurrence, when they happen have a significant impact on populations and regions of its surroundings. Considering the relevance of this issue, this thesis aimed to identify and analyze the dynamics of preparedness and response to emergency situations in a Nuclear Power Plant, trying to understand its evolution over the time and systematizing it, considering the actors involved, processes of organizational learning, innovation and risk communication, considered as crucial for the development and improvement of emergency plans. Concerning preparedness and response to possible emergency situations in this nuclear plant, it was possible not only to confirm the importance of the three processes studied, but also observe that they can be treated and evaluated in an integrated and systematic way. So, it was presented a model that aims to facilitate the understanding of this perspective and enhance the importance of participation and cooperation between all stakeholders (organizations and the local population) within a socio-participatory perspective. To this end, this exploratory research sought for evidences in documents, participation in planning meetings, direct observation of the general exercises of the CNAAA External Emergency Plan of 2013, interviews with some of the actors involved and through the application of a questionnaire among the population of the Praia Vermelha, in Angra dos Reis, Rio de Janeiro.